Parent engagement in early childhood during COVID-19 online education - Çakır, Semanur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The aim of this phenomenological study is to understand parent engagement experiences in online education during the COVID-19 pandemic from the perspectives of early childhood teachers and explore their learning needs to improve parent engagement in online education. The study was conducted with 12 early childhood teachers who delivered online education in Istanbul during the 2020-2021 academic year due to the pandemic. Data were collected through semi-structured interviews and analyzed using thematic approach. Based on the analyses of the lived experiences of early childhood teachers, themes of parent engagement practices in online education; challenges, and opportunities of online education for parent engagement; and learning experiences and needs of teachers in online education emerged. The findings of this study show that parents were engaged in their children's online education during the pandemic period and that parent engagement practices in this period gained a different dimension. However, teachers preferred to conduct parent engagement practices in face-to- face education rather than online education. Although various challenges in parent engagement in online education were encountered, teachers developed specific strategies to overcome these challenges. Lastly, teachers did not receive sufficient training on parent engagement practices in online education during this period and they needed training and support in this regard. This study is significant to document effective methods and approaches in terms of practice, curriculum, and policy with respect to online parent engagement practices in early childhood education.
Keywords: COVID-19 (Disease); Early childhood education.; Education (Early childhood) -- Computer-assisted instruction --